From project to process. Possible trajectories for an urban project based on listening - Marrodán Ciordia, Esperanza (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
For several decades now, the word "participation" has become a leitmotiv in any sphere affecting the public interest. As happened in the 1970s, architecture and urban planning are now trying to define their role in this field. A role that must go far beyond the mere transcription of the will of the citizenry, or the role assigned to it in official participatory processes linked to urban planning. The question is, then, how to incorporate "listening" into projects, be they architectural or urban, without them losing their creative dimension. And in the search for an answer, it is necessary to open our eyes to other ways of doing things. In a context such as the urban context, in which terminology in relation to participation is multiplying exponentially, this article attempts to clarify the different existing processes, finding keys to action aimed at putting the focus back on the person, transforming urban projects into processes capable of listening and interpreting what is heard through proposals that return our cities to the human scale.